A Dictionary of Law - Edited by Law, Jonathan (Oxford Oxford Univ. Press, 2015)
This best-selling dictionary contains over 4,700 clear and concise entries on all aspects of English law. Now in its eighth edition, it has been updated to reflect the very latest legislation. Authoritative and accessible, it is an invaluable guide to legal terminology for students, professionals, and anyone who needs legal terms clearly defined
Keywords: Law -- Great Britain -- Wales